Type 1 Diabetes Mellitus: Issues, Challenges and Opportunities - SR, Chrysanthus Chukwuma (Edelweiss Applied Science and Technology, 2018)
Diabetes is one of the most intensively researched disorders presenting several metabolic alterations, but the basic biochemical aberrations or defects have not been clearly elucidated because the disorder is characteristically of autoimmune disposition. In addition, it is an intricately complex disease that exhibits disparate and distinct outlook and magnitude of pathology with grim susceptibility to gene-environment interactions. Early or invariable developments of deteriorating clinical alterations culminate in expansive socioeconomic costs. Adequate data regarding type 1 diabetes incidence have been from regions with a high or intermediate incidence, particularly in Europe and North America where numerous registries have since been established. There is a paucity of data from Africa Asia, the Caribbean, Central America and South America. The availability of veritable standardized type 1 diabetes incidence data from these low incidence regions is extremely crucial to establish that the presumed broad variation in incidence pertains, and that a low incidence in those regions is exact and not the resultant impact of underestimated incident cases.